POLA PERESEPAN ANTIBIOTIK PADA MANAJEMEN FARINGITIS AKUT DEWASA DI PUSKEMAS - Apsari, Dewi Puspita; Dwicandra, Ni Made Oka; Jaelani, Abdul Khodir (Jurnal Endurance, 2017)
Acute pharyngitis is one of the most common diseases in primary health care, Bali. However, the best management to control the number of antibiotics prescribing in acute pharyngitis is not known. This study aims to determine the best management to control antibiotics prescribing in adult who has acute pharyngitis. This prospective cohort study involved 93 patients aged 12-45 years who had been diagnosed with acute pharyngitis by a physician. Measurements were made on the number of drugs per prescription, frequency antibiotic, quantity antibiotic and DDD antibiotics. Centor Criteria and RADT can reduce the number of antibiotic prescriptions than empirical management in primary health care district X, Bali. Decrease occurred on the the number of drugs per prescription, frequency antibiotic, quantity antibiotic and DDD antibiotics. Management centor criteria and RADT are the best strategies to reduce antibiotic prescription in primary health care distict X, Bali.Â